DISTRIBUSI ROYALTI LAGU DALAM KONSER OLEH LEMBAGA MANAJEMEN KOLEKTIF : SIAPA YANG MEMBAYAR? - I Gusti Ayu Intan Purnamaningrat; I Nyoman Suryana (Yayasan Nusantara Hasana Berdikari, 2025)
This legal research user normative method, with statutory and case approach. The result of this study show that royalty is one of the economic benefits written in Law Number 28 of 2014 concerning Copyright. In the case of concert event, there are two deferent opinions about which legal subject must pay the royalty to the songwriter, through the Collective Management Organization (Lembaga Manajemen Kolektif). Based on Commercial Court Decision No. 92/Pdt.Sus-HKI/Hak Cipta/2024/PN Niaga Jkt.Pst., the payment of royalty is clearly the responsibility of the concert organizer and must be manage through the Collective Management Organization. However, this decision gives compensation directly to the creator and ignores the obligation of the Collective Management Organization. It also put the permorming artist as the defendant which may cause double royalty payment and formal error (error in persona). Judge must consider material justice, legal certanity, and carefulness when making decision, so it will not harm the ecosystem of music industry. The system of royalty payment in concert needs clearer rule and better implementation in court to avoid formal mistake and doube collection. Legal certainty for creators will better if there is more public outreach and also digital record of royalties that can help judge in deciding cae. With this, balance between copyright protection and sustainability of the music industry in Indonesia can be achieved.